Value of direct seeding mulch-based cropping system to field crop farmers in Quebec - Guy Martial Takam Fongang; Jean-François Guay; Charles Séguin (Journal of Agriculture and Food Research)
Direct seeding mulch-based cropping system (DMC) is often touted for providing diverse ecosystem services, but its implementation may impose private costs that often limit its adoption by farmers. This study uses a contingent valuation method and a double hurdle model to estimate Quebec farmers' willingness to accept (WTA) compensation for adopting DMC and to analyze the underlying factors associated with WTA. Results show that farmers would demand, on average, 161 Canadian dollars per hectare as compensation for adopting DMC. Our results also indicate that farmers are willing to convert only 25.5 % of their farm size to DMC. While the adoption of DMC is positively influenced by the ease of implementation and farmers’ perception of DMC yield, the WTA for adopting DMC increases with the perceived risk and yield, as well as farm size. Conversely, it decreases with the age of farmers and if the farmers know a DMC producer. The findings of the study suggest that compensating farmers for adopting DMC is encouraging, but compensation alone may not be sufficient to induce the conversion of entire farms to DMC. The study, therefore, calls for further research to investigate why farmers are willing to convert only a quarter of their farms to DMC.